The Ecologic Validity of Fructose Feeding Trials: Supraphysiological Feeding of Fructose in Human Trials Requires Careful Consideration When Drawing Conclusions on Cardiometabolic Risk - Choo, Vivian L.; Sievenpiper, John L. (Frontiers in Nutrition, 2015)
Background: Select trials of fructose overfeeding have been used to implicate fructose as a driver of cardiometabolic risk. Objective: We examined temporal trends of fructose dose in human controlled feeding trials of fructose and cardiometabolic risk. Methods: We combined studies from eight meta-analyses on fructose and cardiometabolic risk to assess the average fructose dose used in these trials. Two types of trials were identified: 1) substitution trials, in which energy from fructose was exchanged with equal energy from other carbohydrates, 2) addition trials, in which energy from fructose supplemented a diet compared to the diet alone. Results: 64 substitution trials and 16 addition trials were included. The weighted average fructose dose in substitution trials was 101.7 g/d (95% CI: 98.4 - 105.1 g/d), and the weighted average fructose dose in addition trials was 187.3 g/d (95% CI: 181.4 - 192.9 g/d). Conclusions: Average fructose dose in substitution and addition trials greatly exceed national levels of reported fructose intake (49 ± 1.0 g/d) (NHANES 1977-2004). Future trials using fructose doses at real world levels are needed.